2009
DOI: 10.1161/atvbaha.109.196592
|View full text |Cite
|
Sign up to set email alerts
|

Increased PAFAH and Oxidized Lipids Are Associated With Inflammation and Atherosclerosis in Hypercholesterolemic Pigs

Abstract: Objective-To study the association of PAF-acetyl hydrolase (PAFAH) activity with inflammation, oxidative stress, and atherosclerosis in hypercholesterolemic swine. Methods and Results-Cholesterol-rich diet feeding of miniature pigs was associated with an increase in PAFAH activity and an increase of the PAFAH to PON1 ratio. PLA2G7 RNA (coding for PAFAH) expression was increased in blood monocytes and plaque macrophages. Increased PAFAH activity was associated with higher plasma lysophosphatidylcholine and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 56 publications
5
51
0
Order By: Relevance
“…Increased Lp-PLA 2 mass in this setting may represent in vivo evidence for PAF-and/or OxPL-mediated effects on Lp-PLA 2 expression. De Keyzer and colleagues showed that a high-fat diet, which led to increased levels of oxidized LDL, was accompanied by robust increases in Lp-PLA 2 activity ( 55 ). When this response was modeled in a cellular system, the investigators found that oxidized LDL robustly increased expression of Lp-PLA 2 mRNA in THP1 cells and, to a lesser extent, human monocytederived macrophages ( 55 ).…”
Section: Biochemical and Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased Lp-PLA 2 mass in this setting may represent in vivo evidence for PAF-and/or OxPL-mediated effects on Lp-PLA 2 expression. De Keyzer and colleagues showed that a high-fat diet, which led to increased levels of oxidized LDL, was accompanied by robust increases in Lp-PLA 2 activity ( 55 ). When this response was modeled in a cellular system, the investigators found that oxidized LDL robustly increased expression of Lp-PLA 2 mRNA in THP1 cells and, to a lesser extent, human monocytederived macrophages ( 55 ).…”
Section: Biochemical and Structural Propertiesmentioning
confidence: 99%
“…De Keyzer and colleagues showed that a high-fat diet, which led to increased levels of oxidized LDL, was accompanied by robust increases in Lp-PLA 2 activity ( 55 ). When this response was modeled in a cellular system, the investigators found that oxidized LDL robustly increased expression of Lp-PLA 2 mRNA in THP1 cells and, to a lesser extent, human monocytederived macrophages ( 55 ). These combined results suggest that oxidized LDL, PAF, and perhaps OxPL upregulate expression of Lp-PLA 2 in vivo, possibly by increasing mRNA synthesis or stability, resulting in higher protein expression.…”
Section: Biochemical and Structural Propertiesmentioning
confidence: 99%
“…Recently, high levels of PLA2G7 activity were implicated in a swine model of coronary artery disease by increasing inflammation in the necrotic cores of atherosclerotic plaques (73). In this animal model, pharmacological inhibition of PLA2G7 reduced inflammation and disease severity by reducing levels of proinflammatory lysophosphatidylcholine (77).…”
Section: Identifying Primary Candidate Genes Using Eqtlmentioning
confidence: 99%
“…87,88 A recent study on hypercholesterolemic minipigs showed that elevated Lp-PLA 2 activity increased levels of lysophosphatidylcholine, oxidized LDL, and activity of proinflammatory genes in coronary plaque macrophages, which hasten the progression of atherosclerosis. 89 The suggestion of Lp-PLA 2 as a predictor for cardiovascular diseases originated from the West of Scotland Coronary Prevention Study (WOSCOPS) in which each of the 580 men presenting with a coronary event (ie, nonfatal MI, death from CHD, or a revascularization procedure) were matched for age and smoking status with two control subjects (1,160 controls in total) from the same cohort without a coronary event. 90 Lp-PLA 2 , CRP, and fibrinogen levels were measured at baseline along with other traditional risk factors.…”
Section: Lp-plamentioning
confidence: 99%